Salivary free aldosterone awakening response and cardiovascular risk in men with CHD, hypertension, and healthy controls - Gideon, Angelina; von Känel, Roland; Degroote, Cathy; Thomas, Livia; Zuccarella-Hackl, Claudia; Wiest, Roland; Wirtz, Petra H. (Frontiers in Endocrinology, 2026)
BackgroundThe mineralocorticoid hormone aldosterone plays a key role in blood pressure regulation and the development of cardiovascular disease. However, the biological mechanisms that underly prospective associations with negative health outcomes are not fully understood. We compared the awakening response of biologically active salivary aldosterone (AldAR) between male participants with coronary heart disease (CHD), essential hypertension (EHT), and normotension (NT) and additionally examined prospective associations with biological CHD risk factors.MethodsAt baseline, 60 CHD patients, 40 EHT and 44 NT repeatedly assessed the AldAR over two consecutive days. In 97 participants, prospective CHD risk was assessed by changes from baseline to follow-up 2.95 ± 0.07 (SEM) years later in the pro-inflammatory measures interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), and acute phase protein C-reactive protein (CRP), as well as blood lipids in terms of total cholesterol (tChol), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) cholesterol. Potential confounding variables were controlled.ResultsWhereas NT showed the regular AldAR, EHT had higher overall aldosterone levels (p’s < .010, with confounders: p’s < .065) but a flattened AldAR (p = .89). Moreover, CHD patients showed the regular AldAR but on a lower level as compared to NT (p = .002, with confounders: p = .075). Greater AldAR area under the curve independently predicted greater increases in overall inflammatory (p’s ≤ .032) and lipid CHD risk markers (p’s ≤ .089). Significantly greater increases were found for LDL cholesterol (ß = .24, p = .037; with confounders: p’s ≤ .067), and tChol (ß = .26, p = .032; with confounders: p’s ≤ .064). A trend for an association was found for IL-6 (ß = .22, p = .068; with confounders: p’s ≤ .079).ConclusionsWe found evidence for altered AldAR in CHD and EHT with higher AldAR predicting higher CHD risk, particularly in relation to systemic inflammation and dyslipidemia. Elevated AldAR levels may contribute to the pathogenesis of atherosclerotic cardiovascular disease.